Toxicity spectrum of immunotherapy in advanced lung cancer: A safety analysis from clinical trials and a pharmacovigilance system - Yi‐Dan Yan; Ying Zhao; Chi Zhang; Jie Fu; Ying-Jie Su; Xiangli Cui; Er-Li Ma; Bing-Long Liu; Zhi‐Chun Gu; Hou‐Wen Lin (2022)
With the increased use of immune checkpoint inhibitors (ICIs) in advanced lung cancer, adverse events (AEs), particularly immune-related AEs (irAEs), have garnered considerable interest. We conducted a comprehensive assessment of the toxicity profile in advanced lung cancer using multi-source medical data.First, we systematically searched the PubMed, Embase, and Cochrane Library databases (from inception to 10 August 2021) for relevant randomised controlled trials (RCTs) involving ICI-based treatments for advanced lung cancer. The primary outcomes were treatment-related AEs and irAEs, including events that were assigned grade 1-5 and 3-5. The secondary outcomes were grade 5 AEs and irAEs (grade 1-5 and grade 3-5) in specific organs. Network comparisons were conducted for 11 treatments, including chemotherapy (CT), ICI monotherapy (three regimens: programmed death-1 receptor [PD-1] inhibitors, programmed death ligand-1 [PD-L1] inhibitors, and cytotoxic T lymphocyte-associated antigen [CTLA-4] inhibitors), dual-ICI combination therapy (two regimens), and treatment using one or two ICI drugs administered in combination with CT (five regimens). We also conducted a disproportionality analysis by extracting reports of various irAEs associated with ICIs from the FDA Adverse Event Reporting System (FAERS) database. The reporting odds ratios and fatality proportions of different irAEs were calculated and compared. PROSPERO: CRD42021268650.Overall, 41 RCTs involving 23,121 patients with advanced lung cancer were included. Treatments containing chemotherapy increased the risk of treatment-related AEs compared to ICI-based regimens without chemotherapy. Concerning irAEs, PD-L1 + CTLA-4 + CT was associated with the highest risk of grade 1-5 irAEs, followed by two regimens of dual ICI combination, three regimens of ICI monotherapy, and three regimens of one ICI combined with CT. For 3-5 irAEs, CTLA-4 accounted for most AEs. Detailed comparisons of ICI-based treatment options provided irAE profiles based on specific organs/systems and AE severity. Insights from the FAERS database revealed that signals corresponding to pneumonitis, colitis, thyroiditis, and hypophysitis were observed across all ICI regimens. Further analyses of the outcomes indicated that myocarditis (163 of 367, 44.4%), pneumonitis (1610 of 4497, 35.8%), and hepatitis (290 of 931, 31.1%) had high fatality rates.Included RCTs showed heterogeneity in a few clinical factors, and reports derived from the FAERS database might have involved inaccurate data. Our results can be used as a basis for improving clinical treatment strategies and designing preventive methods for ICI treatment in advanced lung cancer.This study was supported by the Research Project of Drug Clinical Comprehensive Evaluation and Drug Treatment Pathway (SHYXH-ZP-2021-001, SHYXH-ZP-2021-006), Clinical Research Innovation and Cultivation Fund of Ren Ji Hospital (RJPY-LX-008), Ren Ji Boost Project of National Natural Science Foundation of China (RJTJ-JX-001), and Shanghai "Rising Stars of Medical Talent" Youth Development Program - Youth Medical Talents - Clinical Pharmacist Program (SHWJRS (2019) 072).